Implementation of Organizational Culture in Building Students' Character: A Qualitative Study in Religious-Based Junior High Schools - Millah Hanifah; Karwanto; Muhammad Sholeh; Amrozi Khamidi; Andi Kristanto; Mohammad Syahidul Haq (EDUJAVARE: International Journal of Educational Research, 2026)
Organizational culture is one of the key factors determining the success of educational institutions, as it influences the behavior, values, and commitment of all school members. This study aims to describe the implementation of organizational culture in fostering students' character development in religion-based junior high schools. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with principals and teachers from two junior high schools. Data analysis was conducted using the stages of data reduction, data display, and conclusion drawing. The findings reveal that organizational culture is built upon religious values, character development, discipline, social responsibility, and achievement, which are internalized through leadership role modeling, habitual practices, school programs, and teachers' professional development. Principals play a pivotal role as change agents by conducting supervision, monitoring, evaluation, and providing continuous motivation to all school members. The implementation of organizational culture is supported by effective communication, teachers' commitment, and parental involvement, while challenges arise from differences in family backgrounds, inconsistent implementation of cultural values, and limited resources. The study concludes that a strong organizational culture significantly strengthens character education and contributes to improving overall school quality.